2010
DOI: 10.1029/2009sw000488
|View full text |Cite
|
Sign up to set email alerts
|

Solar energetic particle cutoff variations during the 29-31 October 2003 geomagnetic storm

Abstract: [1] At low latitudes to midlatitudes the Earth's magnetic field usually shields the upper atmosphere and spacecraft in low Earth orbit from solar energetic particles (SEPs). During severe geomagnetic storms, distortion of the Earth's field suppresses geomagnetic shielding, allowing SEPs access to the midlatitudes. A case study of the 26-31 October 2003 solar-geomagnetic event is used to examine how a severe geomagnetic storm affects SEP access to the Earth. Geomagnetic cutoffs are numerically determined in mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
82
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(85 citation statements)
references
References 30 publications
3
82
0
Order By: Relevance
“…Therefore, our simulation results suggest that the Dst index is not suitable for forecasting the entry of the energetic particles into the magnetosphere at high latitudes. It is compatible with the results of Kress et al (2004Kress et al ( , 2010; Leske et al (2001); Merkin and Goodrich (2007). This may be caused by the fact that Dst index represents the disturbed magnetic field at the dipole equator on the Earth's surface; when the geomagnetic storm is not strong enough to affect the ring current the Dst index does not vary much.…”
Section: Conclusion and Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Therefore, our simulation results suggest that the Dst index is not suitable for forecasting the entry of the energetic particles into the magnetosphere at high latitudes. It is compatible with the results of Kress et al (2004Kress et al ( , 2010; Leske et al (2001); Merkin and Goodrich (2007). This may be caused by the fact that Dst index represents the disturbed magnetic field at the dipole equator on the Earth's surface; when the geomagnetic storm is not strong enough to affect the ring current the Dst index does not vary much.…”
Section: Conclusion and Discussionsupporting
confidence: 77%
“…However, Kress et al (2004) found that the smallest cutoff rigidity did not happen at the time when Dst reached the smallest value but > 10 h prior to the minimum Dst. In addition, Leske et al (2001) and Kress et al (2010) found that in the main phase of a geomagnetic storm there is not an obvious correlation between variations of the Dst index and that of the cutoff rigidity.…”
mentioning
confidence: 99%
“…Furthermore, if the first CME and/or the shocked plasma in front of it contain strong embedded southward-pointing magnetic fields, these southward fields reconnect with the north-directed fields on the front side of the magnetosphere, releasing a large amount of energy. The resulting magnetic storm acts to reduce the geomagnetic field, so that when SEPs accelerated by the second shock reach the neighborhood of the Earth, they may encounter greatly reduced geomagnetic cutoffs and hence can reach an abnormally large fraction of the atmosphere (Leske et al 2001;Kress et al 2010). …”
Section: Solar Proton Events and Coronal Mass Ejectionsmentioning
confidence: 99%
“…5). Variations in SEP access to latitudes can occur on time scales of an hour or less in response to changes in the solar wind dynamic pressure and IMF (Kress et al 2010). For this reason high inclination LEO satellites can at times be vulnerable to SEPs, as well as the International Space Station that has an orbital inclination of 51.64 ı .…”
Section: Sep Effects On Technologymentioning
confidence: 99%